Morbidity Associated with Urinary Diversion in the United States: A Contemporary Evaluation Using the NSQIP Database. Issue 6 (November 2018) - Kovell, Robert C.; Brooks, David C.; Haddad, Devin; Terlecki, Ryan
Abstract : Introduction: : We identified preoperative differences between patients undergoing incontinent vs continent diversion, and compared 30‐day complication outcomes between the 2 procedures. Methods: : Using the NSQIP ® (National Surgical Quality Improvement Program) database we identified patients undergoing urinary diversion incorporating bowel, with or without cystectomy, between 2010 and 2012. We compared preoperative characteristics, surgical parameters and 30‐day postoperative outcomes. We stratified patients based on the continence status of the diversion as incontinent vs continent. Results: : We identified 1, 959 urinary diversions in the NSQIP database, including 1, 568 incontinent diversions (80.0%) and 391 continent diversions (20.0%). Significantly higher rates of chronic obstructive pulmonary disease (9.1% vs 4.3%), previous cardiac surgery (4.3% vs 1.8%), hypertension (63.3% vs 47.1%) and disseminated disease (4.7% vs 2.1%) were noted in patients undergoing incontinent diversion. Patients undergoing continent diversion were significantly more likely to have received preoperative chemotherapy (10.5% vs 5.2%). Operative time was longer for continent diversion (388 vs 336 minutes). Postoperative urinary tract infection (13.8% vs 7.9%) and sepsis rates (11.5% vs 7.9%) were significantly higher with continent diversion, whereas transfusion rates were higher with incontinent diversion (45.2% vs 37.1%). Thirty‐day readmission rates (18.2% vs 15.6%), length of stay (10.2 vs 10.7 days), presence of at least 1 NSQIP captured complication (61.4% vs 64.0%) and mortality (1.5% vs 2.1%) were not statistically different between continent diversion and incontinent diversion. Conclusions: : Urinary diversion incorporating bowel continues to carry a significant risk of postoperative morbidity. While continent diversion offers potential long‐term advantages, these must be balanced against longer operative times and higher rates of postoperative infectious complications.